Beispiel Nr: 06
$ \\ \text{Gegeben: Polynom vom Grad n } \\ \text{Gesucht: } \\ \text{Lösung der Gleichung} \\ $
$\textbf{Aufgabe:}$ $-\frac{1}{4}x^4+\frac{2}{3}x^3=0$
$\textbf{Rechnung:}\\ -\frac{1}{4}x^4+\frac{2}{3}x^3=0\\ x^3(-\frac{1}{4}x+\frac{2}{3})=0 \Rightarrow x=0 \quad \vee \quad-\frac{1}{4}x+\frac{2}{3}=0\\ -\frac{1}{4} x+\frac{2}{3} =0 \qquad /-\frac{2}{3} \\ -\frac{1}{4} x= -\frac{2}{3} \qquad /:\left(-\frac{1}{4}\right) \\ x=\displaystyle\frac{-\frac{2}{3}}{-\frac{1}{4}}\\ x=2\frac{2}{3} \\ \underline{x_1=0; \quad3\text{-fache Nullstelle}} \\\underline{x_2=2\frac{2}{3}; \quad1\text{-fache Nullstelle}} \\$